Peran Inclusive Leadership Dalam Meningkatkan Team Performance Melalui Caring Ethical Climate dan Sense Of Belonging di Era Vuca - Ririn Nur Riastifa; Ikram Yakin; Hasanudin Hasanudin; Pramana Saputra (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Inclusive leadership represents an emerging leadership style increasingly advocated by scholars and practitioners in the VUCA era. Whether this leadership style can better integrate employees and organizations, as well as adapt to complex management in Indonesia’s multicultural state-owned energy enterprises, is the central question addressed in this study. Specifically, this research examines the impact of inclusive leadership on team performance through the mediating roles of caring ethical climate (organizational level) and sense of belonging (individual level). The model was evaluated using cross-sectional data from 280 employees across various regions (Kalimantan 46.1%, Java 22.1%), selected via purposive sampling (minimum six months’ tenure and direct supervision by a supervisor). The results indicate that inclusive leadership has a positive and significant effect on caring ethical climate (β=0.306, p<0.001) and sense of belonging (β=0.598, p<0.001); both variables mediate the relationship with team performance (CEC β=0.167, p<0.001; SB β=0.090, p=0.046). The direct effect was not significant (β=0.072, p=0.306), confirming a full multilevel mediation (R²=0.417). These findings reveal the cross-level mechanisms of inclusive leadership in the diverse SOE context, contributing to the advancement of HRM theory and inclusive leadership practice.